Forecasting the emergency explosive environment with the use of fuzzy data - Zemlianskiy, Oleh; Maladyka, Ihor; Miroshnik, Oleg; Shkarabura, Ihor; Kaplenko, Galina (Eastern-European Journal of Enterprise Technologies, 2017)
We resolved the scientific and technical problem to improve the efficiency of a decision-making processes carried out by a head of emergencies elimination of accidents at potentially dangerous objects by forecasting an emergency explosive environment under conditions of uncertainty. We completed a formalized statement of the problem of identification of the concentration of an explosive gas-air mixture, which makes possible to use fuzzy input and output data. We determined the aspects of solution of the problem of forecasting with a use of expert conclusions in the case of absence or unreliability of input data. We developed the technology of forecasting of parameters of an emergency explosive environment based on the obtained results. The proposed technology can be used in the post-emergency period to clarify fields of an explosive environment. A neuro-fuzzy network can be re-trained in the shortest possible time and used to solve a forecasting problem at all possible points in the zone of explosive environment on the base of the results of measurements of explosive concentration of devices. In addition, this technology can be used to clarify initial values of parameters of an accident, which will improve and objectify a decision making carried out by the head of emergencies elimination